2023
DOI: 10.3390/cells12111512
|View full text |Cite
|
Sign up to set email alerts
|

Korean Red Ginseng-Induced SIRT3 Promotes the Tom22–HIF-1α Circuit in Normoxic Astrocytes

Abstract: Astrocytes play a key role in brain functioning by providing energy to neurons. Increased astrocytic mitochondrial functions by Korean red ginseng extract (KRGE) have been investigated in previous studies. KRGE administration induces hypoxia-inducible factor-1α (HIF-1α) and vascular endothelial growth factor (VEGF) in astrocytes in the adult mouse brain cortex. VEGF expression can be controlled by transcription factors, such as the HIF-1α and estrogen-related receptor α (ERRα). However, the expression of ERRα … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…Interestingly, it was recently reported that Sirt3 regulates the level of HIF-1α in astrocytes [ 70 ], an important transcription factor that along with mitochondrial and cell survival also controls the expression of the VDAC1 gene [ 71 ]. Under reduced oxygen levels, Sirt3 stabilizes a HIF-1α/Tom22 circuit that leads to the expression of Tom20, thereby reactivating mitochondrial functions [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it was recently reported that Sirt3 regulates the level of HIF-1α in astrocytes [ 70 ], an important transcription factor that along with mitochondrial and cell survival also controls the expression of the VDAC1 gene [ 71 ]. Under reduced oxygen levels, Sirt3 stabilizes a HIF-1α/Tom22 circuit that leads to the expression of Tom20, thereby reactivating mitochondrial functions [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was recently reported that Sirt3 regulates the level of HIF-1α in astrocytes [ 70 ], an important transcription factor that along with mitochondrial and cell survival also controls the expression of the VDAC1 gene [ 71 ]. Under reduced oxygen levels, Sirt3 stabilizes a HIF-1α/Tom22 circuit that leads to the expression of Tom20, thereby reactivating mitochondrial functions [ 70 ]. Therefore, also considering these literature data, we can hypothesize that in ALS VDAC1 promotes an adaptation signal to disease-induced stress by stabilizing the Complex I-Sirt3 axis, involving also the TOM complex.…”
Section: Discussionmentioning
confidence: 99%